Sexual and Reproductive Health Rights Among Married Women (Sahayaatra सहयात्रा, 2022)
Sexual and reproductive rights are aspects of human rights. Sexual and reproductive health and rights (SRHR) incorporate the rights of all people, regardless of age, gender and other characteristics, to make choices regarding their sexuality and reproduction. This article has been conducted with the prime objective to examine the decision-making on the use of contraception and the prevalence of sexual violence in Bhojpur Municipality-5 Bhojpur District. This study is based on qualitative, quantitative and mixed research designs. To conduct research, 64 married women of reproductive age are selected as a sample by using the purposive sampling method. In the same way, this article is based on primary and secondary data. Observation and interviews as tools for primary data collection and books, articles, and journals related to sexual violence and sexual rights are used as tools for secondary data collection. Descriptive statistics are used for analysing the data. The study concludes that the sexual and reproductive rights of women are violated by their husbands regarding sex. Likewise, the family prefers sons as a result women are harassed. Women are sexually harassed in society too.